Analisis kinerja keuangan pemerintah wilayah Kota Cirebon (anggaran tahun 2015-2019) - Lutfiyana, Evi; Agus Munandar (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to determine the Financial Performance of the Regional Government of Cirebon City (2015-2019 Budget). This research method uses quantitative descriptive using assessment tools such as the degree of decentralization ratio, independence ratio, effectiveness and growth ratio. Based on the results of the studies are it shows that the financial performance of the local government of Cirebon City is seen from the decentralization ratio has increased from year to year, although the percentage increase is not so large. This shows that the average income of the city of Cirebon from the last 5 years (2015-2019) is 31.16%. Meanwhile, in the 2015 local government of Cirebon City had been financial of independence ratio was lowest situation with a percentage of 32.84, but in the 2018-2019 the ratio of Cirebon City's regional financial independence has increased, being in the medium category and has a participatory relationship. In this regard, the Cirebon City Regional Government can be said to have an ability financial to realize the planned PAD also Cirebon City's PAD growth is relatively up and down. but it that, to always maximize revenue from the existing income capabilities for the benefit of the region and its citizens.